Modeling the process of applying anti-crisis management in the system of ensuring financial security of the enterprise - Oleksandr Sylkin; Myroslav Kryshtanovych; Andryi Zachepa; Sofiia Bilous; Anna Krasko (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
The methodological approach to the application of anti-crisis management in the system of ensuring financial security of the enterprise, unlike the existing ones, summarizes and systematizes the theoretical and methodological features of determining the main stages of anti-crisis management, based on the use of functional modelling methodology and graphical description of processes (IDEF0), significantly increases the ability enterprises adapt to a changing market environment, increase competitiveness and ensure to be stable in financial activities. A complex diagram of the IDEF0 model of applying the anti-crisis management in the process of ensuring the financial security of the enterprise is proposed. It includes input, control, output, mechanism. As a result, a decomposition of the first and the second level context diagrams of the IDEF0 model of anti-crisis management application in the process of ensuring the financial security of the enterprise was formed, which includes, in addition to input, control, output and mechanism, information about the progress of subprocesses and directives for their regulation.
Keywords: D21; D81; L62; G32; 650; financial security; anti-crisis management; enterprise; model; system